Cathepsin K Inhibitors for Osteoporosis: Biology, Potential Clinical Utility, and Lessons Learned - Drake, Matthew T. (Endocr Rev, 2017)
Cathepsin K is a cysteine protease member of the cathepsin lysosomal protease family. Although cathepsin K is highly expressed in osteoclasts, lower levels of cathepsin K are also found in a variety of other tissues. Secretion of cathepsin K from the osteoclast into the sealed osteoclast–bone cell interface results in efficient degradation of type I collagen. The absence of cathepsin K activity in humans results in pycnodysostosis, characterized by increased bone mineral density and fractures. Pharmacologic cathepsin K inhibition leads to continuous increases in bone mineral density for ≤5 years of treatment and improves bone strength at the spine and hip. Compared with other antiresorptive agents, cathepsin K inhibition is nearly equally efficacious for reducing biochemical markers of bone resorption but comparatively less active for reducing bone formation markers. Despite multiple efforts to develop cathepsin K inhibitors, potential concerns related to off-target effects of the inhibitors against other cathepsins and cathepsin K inhibition at nonbone sites, including skin and perhaps cardiovascular and cerebrovascular sites, prolonged the regulatory approval process. A large multinational randomized, double-blind phase III study of odanacatib in postmenopausal women with osteoporosis was recently completed. Although that study demonstrated clinically relevant reductions in fractures at multiple sites, odanacatib was ultimately withdrawn from the regulatory approval process after it was found to be associated with an increased risk of cerebrovascular accidents. Nonetheless, the underlying biology and clinical effects of cathepsin K inhibition remain of considerable interest and could guide future therapeutic approaches for osteoporosis.